Citizenship: A Political or Legal Matter? From Legal - Anthropological Perspective - Gyawali, Chandra Kanta (Patan Pragya, 2020)
Citizenship is a political as well as legal or a constitutional matter. This is also a social right of citizen. The status of being a citizen and the quality of persons, works as a member of a community. Without citizenship, one is denied of rights to live, work, vote, pay taxes and many other things related to his or her rights and duties. Consanguineous relationship, jus soli, naturalization and honorary are considered as major categories of citizenship in Nepal. The citizenship on consanguineous relationship may be linked with the theory of anthropology under the direct line descent, immediate descent, lineal descent, maternal line descent, mediate descent and paternal line descent. In Nepal, a child of a citizen having obtained the citizenship of Nepal by birth prior to the commencement of the Constitution of Nepal should acquire the citizenship of Nepal by descent, if the child’s father and mother (parents) both are citizens of Nepal. Many citizens are in condition of statelessness and deprived of the right to obtain citizenship due to legal, social, administrative, poverty and identities problems of the citizens. Therefore, any citizen of Nepal should not be statelessness or deprived of the right to obtain citizenship on the basis sex, caste, and race, religion social and cultural values.